African Programme for Onchocerciasis Control 1995–2015: Model-Estimated Health Impact and Cost - Coffeng, Luc E.; Stolk, Wilma A.; Zouré, Honorat G. M.; Veerman, J. Lennert; Agblewonu, Koffi B.; Murdoch, Michele E.; Noma, Mounkaila; Fobi, Grace; Richardus, Jan Hendrik; Bundy, Donald A. P.; Habbema, Dik; de Vlas, Sake J.; et al. (PLOS Neglected Tropical Diseases, 2013)
Author Summary In 1995, the World Health Organization launched the African Programme for Onchocerciasis Control (APOC) with the aim to control morbidity due to the parasitic infectious disease onchocerciasis (river blindness). APOC aims to set up sustainable national control programs against onchocerciasis in 16 countries in sub-Saharan Africa, covering over 100 million people who are at risk for infection. The main control strategy is mass treatment with the drug ivermectin, which is donated by the pharmaceutical company Merck. Coordination of the mass treatment programs is made possible by financial contributions from donor and beneficiary countries. We estimated that between 1995 and 2010, APOC has had a huge impact on population health in sub-Saharan Africa, preventing 8.2 million years worth of healthy life from being lost due to disease and mortality, at a cost of about US$257 million. We predicted that this health impact will double during the subsequent five years, at a cost of about US$221 million. This makes APOC one of the most cost-efficient large-scale public health programs in the world. We may expect even greater health gains in the future, given the anticipated extension of the APOC mandate with the aim to eliminate infection where possible.